Utilizing Science and Maqāṣid al-Sharī’ah in Resolving Contemporary Issues of Islamic Family Law - Aslati; Agustar, Armi; Silawati; Arisman; Arafah, Siti (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
Contemporary ijtihad is required in the formulation of new formulas, such as legal protection of the rights of children outside marriage whose biological father is known. Reformulation of Jurisprudence as an analysis of Islamic law must be able to answer socio-cultural problems in the modern era, such as proof of the use of DNA as genealogy. An adaptive formulation of Jurisprudence on contemporary cases by combining science and Maqaṣid al-Shari'ah is analyzed in this article. The resolution of Islamic law by referring to the opinions of the Four Madhhabs of Jurisprudence needs to be approached or juxtaposed with science. A correct understanding of the values contained in the sharia and the application of Maqaṣid al-Shari'ah are indispensable in contemporary ijtihad so that the face of Jurisprudence can dialect with the times. So that the determination of lineage by DNA can be used as a legal reference that is adaptive to science and in accordance with the great objectives of Maqaṣid al-Shari'ah.